Changes in organisation of instep kicking as a function of wearing compression and textured materials. Issue 3 (16th March 2017) - Hasan, Hosni; Davids, Keith; Chow, Jia Yi; Kerr, Graham
Abstract : This study investigated effects of wearing compression garments and textured insoles on modes of movement organisation emerging during performance of lower limb interceptive actions in association football. Participants were six skilled (age = 15.67 ± 0.74 years) and six less-skilled (age = 15.17 ± 1.1 years) football players. All participants performed 20 instep kicks with maximum velocity in four randomly organised insoles and socks conditions, (a) Smooth Socks with Smooth Insoles (SSSI); (b) Smooth Socks with Textured Insoles (SSTI); (c) Compression Socks with Smooth Insoles (CSSI); and (d), Compression Socks with Textured Insoles (CSTI). Results showed that, when wearing textured and compression materials (CSSI condition), less-skilled participants displayed significantly greater hip extension and flexion towards the ball contact phase, indicating larger ranges of motion in the kicking limb than in other conditions. Less-skilled participants also demonstrated greater variability in knee–ankle intralimb (angle–angle plots) coordination modes in the CSTI condition. Findings suggested that use of textured and compression materials increased attunement to somatosensory information from lower limb movement, to regulate performance of dynamic interceptive actions like kicking, especially in less-skilled individuals.